Evaluación en el rendimiento de las extracciones variando ph y cuantificación de antocianinas totales por el método de ph diferencial en el extracto etanólico vaccinium myrtillus “arándano” - Medina Zumarán, Lorenzo (2016)
This report reveals the activities carried out in the Laboratory of Pharmacognosy and pharmacobotany of the Faculty of Pharmacy and Biochemistry; and therefore performance Evaluation extractions varying pH and Quantification of total anthocyanins by the method of differential pH respectively. The study sample was Vaccinium myrtillus "Blueberry". First the sample was selected, then cut into small piece then an ethanolic extract of the filtrate brought to a concentration of 5% was prepared. the method of differential pH was used, with spectrophotometric reading at 510 nm for quantification of total anthocyanins data from the concentration of total anthocyanins where a higher yield was obtained in the concentration of anthocyanins of ethanol extract at pH acid was 8,961 calculated mg / L.